Synthesis, Characterization and Stability Constant study of New Schiff Bases Derived from 2-Amino -2-deoxy Chitosamine and aldehydes with Some Metal Complexes - M. Abbass, Nada (Iraqi Journal of Science, 2023)
Two new Schiff bases (S1,S2) derived from 2-Amino-2-deoxy chitosamine and mnitrobenzaldehyde(S1), and with salicylaldehyde (S2) were prepared andcharacterized using FTIR, UV and mass spectrometry. New complexes of thetransition metal ions Co (II), Ni (II), Pd (II), Pt (II) with the two ligands weresynthesized and their structures were elucidated depending on atomic absorption,FTIR, UV-visible spectra in addition to magnetic susceptibility and electricalconductivity measurement. Metal to ligand [M: L] ratio was obtained for allcomplexes in ethanol using molar ratio method, which gave comparable results withthose obtained for the solid complexes. Stability constant of the complexes weredetermined using spectrophotometric method at 25oC and ionic strength wasmaintained constants using 0.1M KNO3.Stoichometry of the complexes by Job ,smethod showed that metal : ligand ratio is 1:1.